UNIVERSITY SOCIAL RESPONSIBILITY IN STUDENTS OF THE LAST ACADEMIC CYCLE OF A PRIVATE UNIVERSITY OF PERU - Chenet Zuta, Manuel Enrique (2020)
The objective of the study was to measurethe university social responsibility developed by thePrivate University of Huancayo "Franklin Roosevelt"located in Peru, analyzed from the Social Marketing,through the perception of the students of the tenthsemester. The study was basic, univariate and had asimple descriptive design. The variable was dividedinto four dimensions. The population was formedby 140 subjects, distributed in two faculties and fiveprofessional schools. The instrument applied was anattitude scale with 28 items and five response levels.According to the results, an efficient university socialresponsibility level was determined with 78%. Thefour dimensions were rated as efficient accordingto the following figures: ethical and environmentalmanagement (48%), training of responsible citizens(68%), production and dissemination of knowledge(61%), and social participation and humandevelopment (61%).